2005
DOI: 10.1051/radiopro:2005s1-143
|View full text |Cite
|
Sign up to set email alerts
|

A risk related value of spend for saving a statistical life

Abstract: Abstract.A risk related Value of Spend for Saving a Statistical Life (VSSSL) is proposed for cost-benefit studies across the power generation sector, and the nuclear industry in particular. An upper bound on VSSSL is set based on the UK government standard of around £1M or, in particular circumstances, £2M and the observation that excessive spend (probably of the order of more than £5M per statistical life) will cost lives. Above a risk of 10 -3 a -1 it is assumed that VSSSL approaches a value around £2M (broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The average in the UK fluctuated around $US4 million, with a broad range between $US2 and $US10 million (Jackson et al, 2005).…”
Section: How Expensive Is One Avoided Msv Of Low-level Population Expmentioning
confidence: 99%
“…The average in the UK fluctuated around $US4 million, with a broad range between $US2 and $US10 million (Jackson et al, 2005).…”
Section: How Expensive Is One Avoided Msv Of Low-level Population Expmentioning
confidence: 99%
“…A series of values for the value of a life year (VOLY) lost are put forth in the literature, ranging from €21,000 to €56,000 for all age groups. In Canada, Krupnick et al, (176) found a value of a statistical life to be C$0.6 million for people aged 70 and above (€460,000 unadjusted) and in the UK, Jackson et al, (177) found the value of life to be £300,000 (€450,000 unadjusted). The latter estimates are valued using a technique based on willingnessto-pay (for reduction in current and future risk of death) rather than on market earnings.…”
Section: Costmentioning
confidence: 99%